2010
DOI: 10.1186/1471-2105-11-492
|View full text |Cite
|
Sign up to set email alerts
|

The structural and content aspects of abstracts versus bodies of full text journal articles are different

Abstract: BackgroundAn increase in work on the full text of journal articles and the growth of PubMedCentral have the opportunity to create a major paradigm shift in how biomedical text mining is done. However, until now there has been no comprehensive characterization of how the bodies of full text journal articles differ from the abstracts that until now have been the subject of most biomedical text mining research.ResultsWe examined the structural and linguistic aspects of abstracts and bodies of full text articles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 22 publications
6
89
1
Order By: Relevance
“…Further, there is work on intra-textual variation within the BioNLP community, motivated by the need to extract biomedical knowledge not only from abstracts, but also from full-text articles (Cohen et al, 2010). Besides the use of a pre-defined linguistic feature set, in BioNLP also ontologies are widely employed.…”
Section: Related Workmentioning
confidence: 99%
“…Further, there is work on intra-textual variation within the BioNLP community, motivated by the need to extract biomedical knowledge not only from abstracts, but also from full-text articles (Cohen et al, 2010). Besides the use of a pre-defined linguistic feature set, in BioNLP also ontologies are widely employed.…”
Section: Related Workmentioning
confidence: 99%
“…Some journals contained very structured abstracts while others only provided a single sentence or did not state the purpose and/or conclusion of the study. Other investigations have also shown that when using text mining methods, abstracts have different structural and content characteristics from article bodies even when the abstracts are similarly structured [49,50].…”
Section: Final Remarksmentioning
confidence: 99%
“…More recently, the system has also been used to feed information to another text mining system, eFIP, to mine effects of phosphorylation events reported in literature [4,35]. To further enhance the utility of RLIMS-P, we currently aim at making the system generalizable for other PTM types and also applicable to full-text articles, which provides richer biological knowledge beyond abstracts [8].…”
Section: Protein Phosphorylation Iementioning
confidence: 99%